2016
DOI: 10.1177/0309364614547410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of disabilities and activities of daily living of war-related bilateral lower extremity amputees

Abstract: This study and its results confirm that bilateral lower limb amputees have major progressive disabilities in daily activities and their social performance. This should attract the attention of amputees' administrative organizations, social workers, health-care providers and caregiver providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…[ 23 ] Traumatic limb loss mainly affects young individuals and the mean age of the patients in the current study is in consistent with the literature. [ 1 ] It is evident that, with advancing age, cardiovascular consequences of limb loss would affect the whole life of an individual. Therefore, strategies aiming to modulate these risks are of vital importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 ] Traumatic limb loss mainly affects young individuals and the mean age of the patients in the current study is in consistent with the literature. [ 1 ] It is evident that, with advancing age, cardiovascular consequences of limb loss would affect the whole life of an individual. Therefore, strategies aiming to modulate these risks are of vital importance.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic lower limb amputation (LLA) commonly affects young and active individuals who have a long life-expectancy. [ 1 ] It is associated with an increased risk for low back pain, degenerative arthritis, and cardiovascular disease which can reduce overall health quality and physical condition of the wounded persons[ 2 ] Rose et al[ 3 ] and Kurdibaylo[ 4 ] reported that pain, psychological illness, insulin resistance, blood hypercoagulability, and metabolic syndrome were the most frequent handicaps after LLA.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the ADL of veterans with bilateral lower limb amputations showed that the highest level of help was needed for transportation (27.8%) [ 35 ]; however, this was more common in short transfemoral, hip disarticulation and hemipelvectomy amputees. In this study, 54% participated in sporting activities, although 50% of the bilateral lower limb amputees participated in sporting activities [ 36 ]. It was suggested that physical activity should be incorporated into the rehabilitation programs for these patients [ 37 , 38 ]; however, it is important to consider contextual factors, such as the appropriate urban environment, which can cause differences in ADL and IADL.…”
Section: Discussionmentioning
confidence: 99%
“…The validity and reliability of the SF-36 had been tested in Farsi speaking people in Iran before and used for various diseases and disabilities ( 25 ). To determine the severity of amputation, we used the number of remaining functional joints (ankles, knees, hips) in both lower limbs from one to six ( Table 1 ) ( 26 ).…”
Section: Methodsmentioning
confidence: 99%